Evaluation of Traffic Performance in Basuki Rahmat Street, Palu City by Using Road Segmentation Method - Setiawan, Arief; Bakti, Nopkrialtur; Patunrangi, Jurair (Jurnal Teknik Sipil dan Perencanaan, 2021)
Abstract : Basuki Rahmat Street is a National Road with a primary-arterial-function based on the Regional Master Plan of Palu City 2010-2030. The area is focused as a trade and service area which attracts visitors to have economic and social activities. Therefore, each section of the road has other traffic performance. The research was conducted in three road segments: Grand Hero Supermarket, Samsung store, and BCA Bank, and Star Kitchen Electronic Center based on traffic generation of business activity. The study aims to understand Basuki Rahmat street's performance and its activities in each segment. A survey was conducted periodically (early, middle, and end of the month) by taking a workday and a holiday for each period, from 09.00-22.00 WITA. The evaluation method was based on the Indonesian Highway Capacity Manual (IHCM) 1997 urban area on peak hour. The result showed that the Road Segmentation Method (RMS) of Basuki Rahmat street has 0.37 degrees of Saturation (DS) and was included in a B level of service. The differences between DS-RMS and DS on each segment were 0.04. The road segmentation method should be considered to assess the traffic performance of the road link.